Identifying the “Mushroom of Immortality”: Assessing the Ganoderma Species Composition in Commercial Reishi Products - Loyd, Andrew L.; Richter, Brantlee S.; Jusino, Michelle A.; Truong, Camille; Smith, Matthew E.; Blanchette, Robert A.; Smith, Jason A. (Frontiers in Microbiology, 2018)
Species of Ganoderma, commonly called reishi (in Japan) or lingzhi (in China), have been used in traditional medicine for thousands of years, and their use has gained interest from pharmaceutical industries in recent years. Globally, the taxonomy of Ganoderma species is chaotic, and the taxon name G. lucidum has been used for most laccate (shiny) Ganoderma species. However, it is now known that G. lucidum sensu stricto has a limited native distribution in Europe and some parts of China. It is likely that differences in the quality and quantity of medicinally-relevant chemicals occur among Ganoderma species. To determine what species are being sold in commercially-available products, twenty manufactured products (e.g. pills, tablets, teas, etc.) and seventeen “grow your own” (GYO) kits labeled as containing G. lucidum were analyzed. DNA was extracted, and the internal transcribed spacer (ITS) region and translation elongation factor 1-alpha (tef1α) were sequenced with specific fungal primers. The majority (93%) of the manufactured reishi products and almost half of the GYO kits were identified as G. lingzhi. Ganoderma lingzhi is native to Asia and is the most widely cultivated and studied taxon for medicinal use. Illumina MiSeq sequencing of the ITS1 region was performed to determine if multiple Ganoderma species were present. None of the manufactured products tested contained G. lucidum sensu stricto, and it was detected in only one GYO kit. Ganoderma lingzhi was detected in most products, but other Ganoderma species were also present, including G. applanatum, G. australe, G. gibbosum, G. sessile, and G. sinense. Our results indicate that the content of these products vary and that better labeling is needed to inform consumers before these products are ingested or marketed as medicine. Of the 17 GYO kits tested, 11 kits contained Ganoderma taxa that are not native to the United States. If fruiting bodies of exotic Ganoderma taxa are cultivated, these GYO kits will likely end up in the environment. The effects of these exotic species to natural ecosystems needs investigation.